Peningkatan Hasil Belajar IPS Dengan Menerapkan Pembelajaran Kooperatif Model Snowball Throwing Siswa Kelas IV SDN 19 Parepare - Fajar, Fajar; Hasnah, Hasnah (Prodi PGSD FIP UNM, 2017)
The purpose of this study is to investigate the process of implementation of cooperative learning snowball throwing towards learning the material IPS economic activity in the fourth grade students of SDN 19 Parepare and to find out the results of social studies material increase in economic activity in the fourth grade students of SDN 19 Parepare after the implementation of cooperative learning model of snowball throwing. The type of research that is used is action research with a descriptive design . The focus of this research focused on the process of focusing on the process of implementation of social studies learning materials as well as the focus of economic activity that is the result of improving student learning outcomes social studies material economic activity . Subjects were teacher and fourth grade students of SDN 19 Pare-Pare , a total of 30 people , consisting of 13 men and 17 women. Instrument used was a test , observation and documentation. The student learning outcomes in the first cycle of less qualified because there is still an unmet indicator is the number of students who are able to work with a given test is still a little right , but on the second cycle result rising and qualify good . The results showed that an increase in student learning outcomes in social studies class IV material economic activity SDN 19 Parepare by implementing cooperative learning models snowball throwing.Keywords: social studies learning, cooperative learning model, snowball throwing